Measuring Individual Vulnerability - Calvo, C; Dercon, S (Department of Economics (University of Oxford), 2005)
Standard poverty analysis makes statements about deprivation after the veil of uncertainty has been lifted. This implies that there is no meaningful role for risk as part of an assessment of potentially low states of well-being. In this paper, we introduce a concept of vulnerability, as a threat of poverty, with downside risk at its core. More specifically, we define a vulnerability measure as an assessment of the magnitude of the threat of poverty, measured ex-ante, before uncertainty is resolved. We describe the welfare-economic foundations for desirable properties of a vulnerability measure and assess to what extent some measures used in empirical work abide by them. We also present two families of measures that are fully consistent with our axiomatic approach.